PENGARUH KOMPENSASI FINANSIAL, KONFLIK PERAN, KETIDAK JELASAN PERAN, TERHADAP KEPUASAN KERJA AUDITOR - Putu Ayu Dyah Julianti Sunadi Safitri; I Putu Nuratama (Hita Akuntansi dan Keuangan, 2021)
This research study aims to determine the effect of financial competence, role conflict, role ambiguity, on job satisfaction of auditors who work at the public accounting firm in Denpasar, Bali, which is registered in the IAPI (Indonesian Public Accountants Association). By analyzing and testing hypotheses. Concurrently or partially, this research was conducted on 83 auditors who worked for between one year and had audited at least 1 audit at a public accounting firm in 2019. The research method used in this study was descriptive analysis. The method used in this study is a non-probability sampling method with the technique of the sampling method, purposive sampling. The results of this study indicate that financial compensation, Role Conflict, role ambiguity, simultaneously and partially have an influence on job satisfaction of auditors who work at the Public Accounting Firm in Denpasar, Bali, which is listed in IAPI (Indonesian Public Accountants Association) in 2019. Data collection conducted with questionnaires submitted directly. The number of questionnaires distributed was 73 copies, but only 50 questionnaires were returned. The results showed that financial compensation had a significant effect on auditor job satisfaction, role conflict had no significant effect on auditor job satisfaction, and role ambiguity had a significant effect on auditor satisfaction